{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# Rudin_3 - Numerical Sequences and Series Written by Men-Gen...

This preview shows pages 1–5. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Numerical Sequences and Series Written by Men-Gen Tsai email: [email protected] 1. Prove that the convergence of { s n } implies convergence of {| s n |} . Is the converse true? Solution: Since { s n } is convergent, for any > 0, there exists N such that | s n- s | < whenever n ≥ N . By Exercise 1.13 I know that || s n |-| s || ≤ | s n- s | . Thus, || s n |-| s || < , that is, { s n } is convergent. The converse is not true. Consider s n = (- 1) n . 2. Calculate lim n →∞ ( √ n 2 + n- n ). Solution: √ n 2 + n- n = n √ n 2 + n + n = 1 q 1 /n + 1 + 1 → 1 2 as n → ∞ . 3. If s n = √ 2 and s n +1 = q 2 + √ s n ( n = 1 , 2 , 3 ,... ) , prove that { s n } converges, and that s n < 2 for n = 1 , 2 , 3 ,... . Proof: First, I show that { s n } is strictly increasing. It is trivial that s 2 = q 2 + √ s 1 = r 2 + q √ 2 > √ 2 = s 1 . Suppose s k > s k- 1 when 1 k < n . By the induction hypothesis, s n = q 2 + √ s n- 1 > q 2 + √ s n- 2 = s n- 1 By the induction, { s n } is strictly increasing. Next, I show that { s n } is bounded by 2. Similarly, I apply the induction again. Hence { s n } is strictly increasing and bounded, that is, { s n } converges. 4. 5. 6. 7. Prove that the convergence of ∑ a n implies the convergence of X √ a n n if a n ≥ 0. Proof: By Cauchy’s inequality, k X n =1 a n k X n =1 1 n 2 ≥ k X n =1 a n √ a n n for all n ∈ N . Also, both ∑ a n and ∑ 1 n 2 are convergent; thus ∑ k n =1 a n √ a n n is bounded. Besides, √ a n n ≥ 0 for all n . Hence ∑ √ a n n is convergent. 8. 9. Find the radius of convergence of each of the following power series: ( a ) X n 3 z n , ( b ) X 2 n n ! z n , ( c ) X 2 n n 2 z n , ( d ) X n 3 3 n z n . 2 Solution: (a) α n = ( n 3 ) 1 /n → 1 as n → ∞ . Hence R = 1 /α = 1. (b) α n = (2 n /n !) 1 /n = 2 / ( n !) 1 /n → 0 as n → ∞ . Hence R = + ∞ . (c) α n = (2 n /n 2 ) 1 /n → 2 / 1 = 2 as n → ∞ . Hence R = 1 /α = 1 / 2. (d) α n = ( n 3 / 3 n ) 1 /n → 1 / 3 as n → ∞ . Hence R = 1 /α = 3. 10. 11. Suppose a n > 0, s n = a 1 + ... + a n , and ∑ a n diverges. (a) Prove that ∑ a n 1+ a n diverges. (b) Prove that a N +1 s N +1 + ... + a N + k s N + k ≥ 1- s N s N + k and deduce that ∑ a n s n diverges. (c) Prove that a n s 2 n ≤ 1 s n- 1- 1 s n and deduce that ∑ a n s 2 n converges. (d) What can be said about X a n 1 + na n and X a n 1 + n 2 a n ? Proof of (a): Note that a n 1 + a n → ⇔ 1 1 a n + 1 → ⇔ 1 a n → ∞ ⇔ a n → as n → ∞ . If ∑ a n 1+ a n converges, then a n → 0 as n → ∞ . Thus for some = 1 there is an N 1 such that a n < 1 whenever n ≥ N 1 . Since ∑ a n 1+ a n converges, for any > 0 there is an N 2 such that a m 1 + a m + ... + a n 1 + a n < 3 all n > m ≥ N 2 . Take N = max( N 1 ,N 2 ). Thus > a m 1 + a m + ... + a n 1 + a n > a m 1 + 1 + ... + a n 1 + 1 = a m + ... + a n 2 for all n > m ≥ N . Thus a m + ... + a n < 2 for all n > m ≥ N . It is a contradiction. Hence ∑ a n...
View Full Document

{[ snackBarMessage ]}

### Page1 / 17

Rudin_3 - Numerical Sequences and Series Written by Men-Gen...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online